The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1413-41522012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da aplicação de água residuária de suinocultura no solo e na qualidade dos seus lixiviados

Abstract: Este trabalho avalia o comportamento da água residuária de suinocultura, quanto aos seus efeitos no solo e na qualidade dos seus lixiviados. Na incubação do solo com efluente, foram utilizadas 48 unidades experimentais no total com taxas de aplicação de 0, 50, 100 e 150 m³.ha-1. O pH do solo e lixiviados após asdiferentes taxas de aplicação permaneceu ácido e os valores de amônia nos argissolos apresentaram valores menores do que no solo testemunha enquanto que nos nitossolos houve aumento em função das taxas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
5
1
3
Order By: Relevance
“…The lowest concentrations of NO3 -, represented by the lower dashed line of box-plots, presented results below 3.0 mg L -1 , being lower than the 14.6 mg L -1 found by Santos et al (2014) after application of 137.1 kg ha -1 of nitrogen, derived from swine wastewater, in soils columns; and from 12.6 mg L -1 obtained by Bolzani et al (2012) after dosing of 67.2 kg ha -1 of nitrogen applied through swine wastewater (SSW). Esterhuizen et al (2012) evaluated groundwater from 75 dairy farms in Mangaung, South Africa, and found that 49.3% of the wells had NO3 -concentrations higher than 10 mg L -1 , which, according to the authors, are consequences of poor management practices in the disposal of wastewater in the soils of the region.…”
Section: Resultscontrasting
confidence: 54%
See 4 more Smart Citations
“…The lowest concentrations of NO3 -, represented by the lower dashed line of box-plots, presented results below 3.0 mg L -1 , being lower than the 14.6 mg L -1 found by Santos et al (2014) after application of 137.1 kg ha -1 of nitrogen, derived from swine wastewater, in soils columns; and from 12.6 mg L -1 obtained by Bolzani et al (2012) after dosing of 67.2 kg ha -1 of nitrogen applied through swine wastewater (SSW). Esterhuizen et al (2012) evaluated groundwater from 75 dairy farms in Mangaung, South Africa, and found that 49.3% of the wells had NO3 -concentrations higher than 10 mg L -1 , which, according to the authors, are consequences of poor management practices in the disposal of wastewater in the soils of the region.…”
Section: Resultscontrasting
confidence: 54%
“…The variations observed between the first and third quartiles show that the percolated pH did not undergo major alterations, a result that corroborates with those obtained by Maggi et al (2011) who obtained fluctuations between 7.0 and 7.3 pH in percolates after maximum application of 300 m 3 ha -1 of swine wastewater (SSW) and Trevisan et al (2013) who studied the quality of the percolate with the application of swine wastewater (SSW) do not finding differences in the percolated pH between the doses of 150 and 600 kg ha -1 of nitrogen. However, Bolzani et al (2012) evaluated the percolated in Argisol fertirrigated with SSW, they observed an increase of the percolated pH in function of the application rates, mainly after application of 150 m³ ha -1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations